Role of phytomelatonin responsive to metal stresses: An omics perspective and future scenario - Ali, Skhawat; Gill, Rafaqat Ali; Shafique, Muhammad Sohaib; Ahmar, Sunny; Kamran, Muhammad; Zhang, Na; Riaz, Muhammad; Nawaz, Muhammad; Fang, Rouyi; Ali, Basharat; Zhou, Weijun (Frontiers in Plant Science, 2022)
A pervasive melatonin (N-acetyl-5-methoxytryptamine) reveals a crucial role in stress tolerance and plant development. Melatonin (MT) is a unique molecule with multiple phenotypic expressions and numerous actions within the plants. It has been extensively studied in crop plants under different abiotic stresses such as drought, salinity, heat, cold, and heavy metals. Mainly, MT role is appraised as an antioxidant molecule that deals with oxidative stress by scavenging reactive oxygen species (ROS) and modulating stress related genes. It improves the contents of different antioxidant enzyme activities and thus, regulates the redox hemostasis in crop plants. In this comprehensive review, regulatory effects of melatonin in plants as melatonin biosynthesis, signaling pathway, modulation of stress related genes and physiological role of melatonin under different heavy metal stress have been reviewed in detail. Further, this review has discussed how MT regulates different genes/enzymes to mediate defense responses and overviewed the context of transcriptomics and phenomics followed by the metabolomics pathways in crop plants.